Sports-Related Cervical Spine Injury: A Series of Two Cases with Literature Review - Ranjan, Nitish; Maurya, Ved Prakash; Bhaisora, Kamlesh Singh; Srivastava, Arun Kumar (Indian Journal of Neurotrauma, 2024)
Sports-related cervical injuries pose a significant concern in the realm of sports medicine, affecting athletes across various disciplines and levels of competition. Cervical injuries in sports primarily result from a combination of high-impact forces, sudden acceleration–deceleration movements, and improper techniques. Common cervical injuries include sprains, strains, fractures, and more severe conditions such as cervical spine dislocations. The mechanisms underlying sports-related cervical injuries involve complex interactions between biomechanical forces, player dynamics, and environmental factors. Understanding the biomechanics of these injuries is crucial for developing effective preventive strategies. This study highlights the mechanism of injury, primary intervention including transport of athletes, and medical and surgical management with the help of two such cases managed in a single institute in this year, 2023. By addressing the multifaceted aspects of these injuries, the sports community can strive toward creating a safer environment for athletes and minimizing the impact of cervical injuries on their overall well-being and athletic performance.
Keywords: sports; cervical; mechanism; subluxation; fixation